Home Visit Berbasis Sistem Informasi Manajemen Telenursing - Padila Padila; Liza Fitri Lina; Henni Febriawati; Bintang Agustina; Riska Yanuarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to analyze the description of procurement of nursing home information management systems for telenursing home visits at hospitals. Dr. M. Yunus Bengkulu. The research design that researchers use modifies the research theory (R) and development (D). Development of telenursing technology based on BAN technology (body area network) can provide monitoring results in real time and connected with WSN (wireless sensor network) transmission through integration with deviceendusers (laptops) which in design and implementation can be used in rural and remote areas. The results of the study there is a system design program that has the advantage of being able to be used to send medical data of patients, the main complaints, the type of disease they feel (mild, moderate and severe), visualization of data in image, sound and text, even video can be used as a detector for patient health digital based via video mail, and family health history with multimedia medical records techniques that are connected to the hospital health care center. Dr. M. Yunus Bengkulu. The research was directly tested on nurses to gain nurses' understanding in using telenursing. Conclusions, which are obtained from this study are the enthusiasm of nurses in accepting new challenges in providing telenursing services is very high, it can have an impact on the ability to improve effective communication between nurses and patients. Keywords: Home Visit Telenursing, Development, SIM